Electronically Tunable Transimpedance Instrumentation Amplifier Based on OTRA. (18th December 2012) - Pandey, Rajeshwari; Pandey, Neeta; Paul, Sajal K.
Abstract : Operational transresistance amplifier (OTRA) is the most suitable analog building block (ABB) for transimpedance type signal processing due to its very nature of current input and voltage output. In this paper, OTRA-based transimpedance instrumentation amplifier (TIA) is presented. It provides high differential gain and bandwidth, which is independent of gain. It also offers high common-mode rejection ratio (CMRR). The amplifier gain can be controlled electronically by implementing resistors using MOS transistors operating in linear region. The circuit can be made fully integrated. The proposed circuit is insensitive to parasitic input capacitances and input resistances due to the internally grounded input terminals of OTRA. Theoretical analysis is verified through PSPICE simulations and experimentation.